The effects of phosphorus and lime application upon phosphorus adsorption in a Dark-Red Latosol (Oxisol) - Dynia, José Flavio; Camargo, Otávio Antônio de (Pesquisa Agropecuaria Brasileira, 1997)
The effect of sequential applications of phosphorus, and phosphorus + lime, upon phosphorus adsorption parameters of a "cerrado" Dark-Red Latosol (Oxisol) was evaluated. The phosphorus (1,530 kg P2O5/ha) and the lime (5.5 t/ha) were applied along a series of seventeen alternate crops - rice (5), bush-bean (6), wheat (4) and corn (2) - during a six and half-year period. Phosphorus was split-applied at a rate of 90 kg P2O5/ha per crop. Lime was applied twice: before the first crop (2.5 t/ha), and between the ninth and the tenth crops (3.5 t/ha). Both phosphorus and phosphorus plus lime treatments significantly reduced the soil maximum adsorption capacity for P, but did not affect the P-soil retention energy.